Evaluating the Impact of Structured Educational Interventions on Cervical Cancer Awareness and Prevention: A Pre-Experimental Study Among Rural Women in Gurugram, Haryana, India - Vengathattil, Sunish (Journal of Educational Research and Policies, 2025)
Cervical cancer is the second most common cancer among Indian women. Prevention and early detection can help reduce the incidence of cervical cancer. Taking care of health needs of the people and preventing diseases is a major concern for health, professionals. Planned teaching programme is one of the most effective teaching strategies, which can be used for improving the knowledge of people. Aim: The aim of this study was to find out the effectiveness of a planned teaching programme in improving the knowledge of women in prevention and early detection of cervical cancer. Material and Methods: Pre experimental design was used to assess the Effectiveness of Planned Teaching Programme (PTP) on knowledge regarding early detection and prevention of cervical cancer. Purposive sampling techniques were used to select 60 women in selected village in Gurugram. Informed written consent was taken from selected women. A structured questionnaire was administered to assess the knowledge on early detection and prevention of cervical cancer. The collected data was analyzed by using descriptive statistics and inferential statistics. Frequency and percentage distribution was used for demographic variables and assessing the knowledge on early detection and prevention of cervical cancer. Chi- square test was used to find out association between knowledge on early detection and prevention of cervical cancer among women and selected demographic variables. Result: The finding of the study revealed that pre test knowledge 35% had poor, 60% had average,5% had good knowledge regarding early detection and prevention of cervical cancer. Post test knowledge 0% had poor, 25% had average, 75% had good knowledge regarding early detection and prevention of cervical cancer. Knowledge was significantly associated with religion0.02 at significance of p<0.05 level. No association was found between knowledge and other demographic variables like age, education, occupation, marital status, number of children, health information. Conclusion: Planned teaching programme will be effective in improving knowledge regarding early detection and prevention of cervical cancer among women in selected villages in Gurugram.